2018
DOI: 10.1097/md.0000000000012352
|View full text |Cite
|
Sign up to set email alerts
|

No association between C-reactive protein and depressive symptoms among the middle-aged and elderly in China

Abstract: The depressive symptoms have been associated with increased disabilities, and the depressive symptoms-related elevation of high C-reactive protein (CRP) has been proposed as a possible mechanism. We examined the relations between CRP and depressive symptoms among the middle-aged and elderly in China.A longitudinal sample of the middle-aged and elderly (4404 men and 5055 women) who were interviewed in the 2011 China Health and Retirement Longitudinal Study was used. A multivariate logistic regression analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 36 publications
2
21
1
2
Order By: Relevance
“…Table 1 presents the baseline characteristics of the sample for all studied variables, most of which were based on our previous study. [ 3 , 20 , 21 ]…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 presents the baseline characteristics of the sample for all studied variables, most of which were based on our previous study. [ 3 , 20 , 21 ]…”
Section: Methodsmentioning
confidence: 99%
“…In total, 7119 participants who effectively completed the questionnaires were included in our research. The baseline of demographic variables was shown in Table 1, and most variables based on our previous studies [40][41][42][43][44] Table 1 showed the relationship between various characteristics and BP levels in the participants. Significant differences in distribution were observed between blood pressure status in the men in all of the variables, except cigarette smoking, alcohol consumption, eating habit, social and leisure activities, physical exercise, hepatitis history, anti-diabetic medication, and HDL-C. Age, CRP, HbA1c, FPG, LDL-C, BMI, TG, SUA, SBP, and DBP were significantly higher in hypertension than those in the normotension, whereas, eGFR level were lower in hypertension than that in the normotension.…”
Section: Resultsmentioning
confidence: 99%
“…Variables like age, educational levels (four categories, illiterate, less than elementary school, high school, and above vocational school), marital status (dichotomous variables, the single and married), place of residence (dichotomous variables, rural and urban), cigarette smoking (three categories, no, former smoke, and current smoke), alcohol consumption (three categories, no, less than once a month, and more than once a month), eating habit (three categories, ≤two meals per day, three meals per day, and ≥ four meals per day), social and leisure activities (dichotomous variables, no and yes), accidental injury (dichotomous variables, no and yes), physical exercise (three categories, no physical exercise, less than physical exercises, and regular physical exercises), history of liver disease (dichotomous variables, no and yes), history of cardiovascular diseases (dichotomous variables, no and yes), antidiabetic medication (dichotomous variables, no and yes), antilipidemic medication (dichotomous variables, no and yes), and antihypertensive medication (dichotomous variables, no and yes) were obtained using a self-reported questionnaire, and most variables based on our previous studies [40][41][42][43][44].…”
Section: Self-reported Factorsmentioning
confidence: 99%
“…Tab. 3 zeigt die Studienergebnisse in Bezug auf die basalen Konzen trationenderEntzündungsmarkerCRP,IL-6undTNF-α.Diedeutli che Mehrheit der Studien, welche den Zusammenhang von Depres sivität und CRPSpiegeln untersuchten, kam zu dem Ergebnis, dass die CRPSpiegel bei Frauen oft unabhängig von deren Depressivität waren, während eine schwere Depressionssymptomatik bei Män nern mit erhöhten CRPSpiegeln assoziiert ist [52][53][54][55][56][57][58][59][60], vor allem in VerbindungmitsozialerIsolation [61].Amzweithäufigstenwurde repliziert, dass CRP nur bei Frauen positiv mit Depression korre liert [62][63][64][65]. Darüber hinaus existieren vereinzelte andere Befun de [66][67][68].Sehrhäufigkonntedarüberhinausrepliziertwerden, dass die mittleren CRPSpiegel bei Frauen generell höher ausfal len als bei Männern [52-54, 58, 66], auch unter Probanden mit er höhter Depressionssymptomatik [62].…”
Section: Entzündungsparameterunclassified
“…Als weitere potenzielle zentra leEinflussfaktorenfürdenZusammenhangvonDepressionund HHNA bzw. Entzündungsparametern konnten unter anderem das Alter der Probanden, die Art und Schwere der Depressionssympto meunddieKörperkonstitution(z.B.BMI)identifiziertwerden [29,47,51,60,61,71]. Dies macht deutlich, dass eine große Anzahl an konfundierenden Variablen die Zusammenhänge zusätzlich trü ben und in zukünftigen Studien sollten diese zentralen Variablen immer mitberücksichtigt und entsprechende Assoziationen dafür kontrolliert werden.…”
Section: Zusammenfassung Der Befundeunclassified